Comer e beber as paisagens: alimentação e turismo nos restaurantes de Vila Real - Pereiro, Xerardo; Tibério, Manuel Luís; Rodrigues, Vítor (Trabalhos de Antropologia e Etnologia, 2020)
In this work, we proceed to a reflection on the relationship between food and tourism, with restaurants in the background. Based on a case study carried out in the small town of Vila Real (Northern Portugal), capital of the district of Vila Real, the implications of this relationship are deepened in a perspective of territorial development with greater sustainability.